IN VITRO SOLUBILITY ENHANCEMENT OF ONDANSETRON HCL BY PREPARATION OF ONDANSETRON-POROUS SILICA COMPOSITES - BADER, QASIM ALLAWI; ALI, WEDAD K.; AL-SAADY, FOUAD A. A. (International Journal of Applied Pharmaceutics, 2025)
Objective: To enhance the solubility of Ondansetron (OND), a wet impregnation approach utilizing porous silica was explored to produce OND-Porous silica composite, and then UV spectrophotometric protocols were employed to evaluate the equilibrium solubility and the loading capacity of the obtained preparation. Methods: Ondansetron and porous silica composites were synthesized via the wet impregnation method and subsequently subjected to evaluation. for their surface morphology and roughness of was carried out using Scanning Electron Microscope (SEM) and Atomic Force Microscopy (AFM), along with X-Ray defrractometry (XRD), Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA), and nitrogen adsorption and desorption experiments. Results: The solubility profile of OND was maximized through the development of OS3 composite formula which was 3-4 times higher than the former. Furthermore, the TGA and UV evaluation tests of the enhanced OS3 formula revealed an improvement in the loading capacity of the drug (45-48%). To confirm the successful introduction of OND within the porous of silica structure, XRD analysis exploited, showing a significant alteration in OND amorphousness. The XRD data confirmed a notable reduction in silica surface area (from 68.239 m2/g to 26.226 m2/g), pore width (from 46.13 nm to 1.21 nm), and porous volume (from 1.2229 cm3/g to 0.178 cm3/g) following the loading of drug on silica. Conclusion: It was concluded that this approach was able to introduce a promised method for enhancing the solubility of OND to produce a powder with physical properties, enable to establish further processing steps like tablet compression or even transdermal patch fabrication.